Unlocking the secrets of Sensex returns: the crucial role of valuation in different time horizons - Pradeep, K. V.; Simmy, K. (University of Jaffna, 2024)
The study attempts to analyse the return generated by BSE Sensex for the past 24 years and the risk associated with investments in different periods. The study also explores the relationship between valuation ratios and Sensex returns. For this purpose, Sensex data (Index value, Price-earnings ratio, Price-to-book value) for 24 years (1998 to 2022) is taken. The data is analysed using Compounded Annual Growth Rate (CAGR) for different time periods along with standard deviation to assess the return and risk. The association between valuation ratios and index return is analysed using correlation analysis and ANOVA. The results show that risk of investment can be substantially reduced by increasing the holding period of security. The study also reveals that index returns will vary based on the valuation ratio at the point of entry.
Keywords: Index Valuation; Price Earnings Ratio; Price to Book Ratio